1980
DOI: 10.1267/ahc.13.72
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical Studies on the Intramembranous Particles of Erythrocyte Membranes

Abstract: The chemical composition and the function of intramembranous particles (IMP) of erythrocyte membranes were examined. Firstly, the sulfhydryl (SH) groups detected by the Fast Blue BBN method on ultrathin sections of rabbit erythrocyte ghosts were found to show a correlative distribution with IMP. Secondly, after treating human erythrocyte ghosts with mercuric chloride, IMP appeared to have become larger than the controls. The mean diameter of IMP was approximately 165 A on the P face and 160 A on the E face for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…in 1972 (203)showed that there was a relationship between the external surface components of glycophorin and band-3 protein in erythrocytes and the intramembrane particles seen in FFE preparations. da Silva in 1972 (204), Elgsaeger and Branton in 1974 (205), and others more recently (206,207) have presented evidence of IMP aggregation phenomena . These are altered when spectrin is extracted from erythrocyte ghosts, which is interpreted as indications of the transmembrane connections of glycophorin and band 3 with spectrin.…”
Section: The Intramembrane Particlementioning
confidence: 94%
“…in 1972 (203)showed that there was a relationship between the external surface components of glycophorin and band-3 protein in erythrocytes and the intramembrane particles seen in FFE preparations. da Silva in 1972 (204), Elgsaeger and Branton in 1974 (205), and others more recently (206,207) have presented evidence of IMP aggregation phenomena . These are altered when spectrin is extracted from erythrocyte ghosts, which is interpreted as indications of the transmembrane connections of glycophorin and band 3 with spectrin.…”
Section: The Intramembrane Particlementioning
confidence: 94%
“…24). Tanaka and Ogawa (37) and Fujimoto and Ogawa (8) reported that the reaction products of SH groups corresponded to the intramembranous particles observed in the freeze-etching replicas of erythrocyte membranes. The reaction disappeared after protease digestion (9,37).…”
Section: Discussionmentioning
confidence: 96%
“…However, the use of enzyme cytochemistry for the study of the ultrastructural localization of enzyme molecules in this area has not received considerable attention. Although only a few applications of enzyme cytochemical technique to freeze-fracture electron microscopy have been reported, these attempts have not been fully successful [7,8]. The major reason for this is that the reaction products (e.g.…”
Section: Discussionmentioning
confidence: 99%